How Much Is Enough? Shaping the Defense Program, 1961-1969 - Enthoven, Alain C. (RAND Corporation, 1971)
Originally published in 1971, and now published with a new foreword, this is a book of enduring value and lasting relevance. The authors detail the application, history, and controversies surrounding the Planning, Programming, and Budgeting System (PPBS), used to evaluate military needs and to choose among alternatives for meeting those needs.